Caracterização de soluções de quitosana por espalhamento dinâmico de luz - Oliveira, Victor Anderson Veríssimo de (2012)
Dynamic light scattering was used to monitor relaxation processes in chitosan solutions at concentrations within the semi-dilute and concentrated regimes, Kowhlrausch-Williams-Watts (KWW) equation being successfully fitted to intensity correlation function data. The dependence of KWW equation parameters on chitosan concentration indicated that an increase in concentration from semi-dilute to concentrated regimes resulted in narrowing the distribution of relaxation rates; temperature dependence indicated the relaxation process as described as an energy activated process, whose parameters were function of the interaction between chitosan chains (enthalpy of activation) and rigidity of chitosan conformations (pre-exponential factor)